2022
DOI: 10.1177/00953997211073948
|View full text |Cite
|
Sign up to set email alerts
|

‘I don’t know nothing about that’: How “learning costs” undermine COVID-related efforts to make SNAP and WIC more accessible

Abstract: Scholars have focused on administrative burden or the costs of claiming public benefits. These costs, such as learning, psychological, and compliance costs can discourage program participation and benefit redemption. Using 60 in-depth qualitative interviews with participants of the SNAP and WIC programs, we offer thick descriptions of how beneficiaries experience compliance, learning, and redemption costs—a subset of learning costs regarding how to redeem benefits—amidst COVID-19 policy changes. Although polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Despite the implementation of program modifications during this time, benefit redemption challenges were common. Consistent with the results of previous research, many participants had difficulty finding WIC-approved items in stores due to a lack of shelf labeling and low stock of WIC foods [ 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 ]. Some participants also experienced confusion when determining which brands and sizes were WIC-eligible [ 17 , 24 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Despite the implementation of program modifications during this time, benefit redemption challenges were common. Consistent with the results of previous research, many participants had difficulty finding WIC-approved items in stores due to a lack of shelf labeling and low stock of WIC foods [ 10 , 11 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 ]. Some participants also experienced confusion when determining which brands and sizes were WIC-eligible [ 17 , 24 ].…”
Section: Discussionsupporting
confidence: 84%
“…A large body of previous research demonstrates that WIC participants often face difficulties with in-store benefit redemption [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Several factors have been shown to contribute to these redemption challenges including a lack of accurate, consistent shelf labeling [ 10 , 11 , 17 , 18 , 19 , 20 , 21 ], low stock of WIC-approved foods [ 11 , 15 , 16 , 20 , 22 , 23 ], issues at the checkout (i.e., perceived stigma and long waiting times) [ 10 , 11 , 17 , 24 ], confusion about WIC-eligible items (i.e., brands and sizes) [ 17 , 24 ], and inconsistencies between the register and the information participants receive from the program/WIC apps, particularly following program and policy changes [ 20 , 22 , 24 ]. These challenges were exacerbated by the COVID-19 pandemic and related issues such as global grocery retail shortages and rising food and household costs [ 1 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found that changes in the CVB amount over the period of June to December 2021, including a one-month temporary decrease in benefits, created a notable amount of confusion and uncertainty about redeeming CVB among North Carolina participants. These challenges are similar to the learning costs [ 71 , 72 ] associated with public assistance programs that present major barriers to use, and these barriers should be considered by policymakers when designing future emergency food response programs. Overall, there are still a variety of barriers to using the CVB and WIC benefits more generally that urgently need to be addressed for WIC to have the greatest possible impact on reducing diet-related disease and fruit and vegetable consumption disparities by income, race/ethnicity, and rurality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that changes in the CVB amount over the period of June to December 2021, including a one-month temporary decrease in benefits, created a notable amount of confusion and uncertainty about redeeming CVB among North Carolina participants. These challenges are similar to the learning costs [69,70] associated with public assistance programs that present major barriers to use and these barriers should be considered by policymakers when designing future emergency food response programs. Overall, there are still a variety of barriers to using the CVB, and WIC benefits more generally, that urgently need to be addressed for WIC to have the greatest possible impact on reducing diet-related disease and fruit and vegetable consumption disparities by income, race/ethnicity, and rurality.…”
Section: Discussionmentioning
confidence: 99%